Brill's companion to ancient Macedon : studies in the archaeology and history of Macedon, 650 BC-300 AD - Lane Fox, Robin, 1946- (Brill's Companions to Classical Studies., 2011)
In the past 35 years our archaeological and epigraphic evidence for the history and culture of ancient Macedon has been transformed. This book brings together the leading Greek archaeologists and historians of the area in a major collaborative survey of the finds and their interpretation, many of them unpublished outside Greece. The recent, immensely significant excavations of the palace of King Philip II are published here for the first time. Major new chapters on the Macedonians' Greek language, civic life, fourth and third century BC kings and court accompany specialist surveys of the region's art and coinage and the royal palace centres of Pella and Vergina, presented here with much new evidence. This book is the essential companion to Macedon, packed with new information and bibliography which no student of the Greek world can now afford to neglect.